MUHAMMAD’S LINGUISTIC CHARACTERS IN THE QURAN: A SOCIOLINGUISTIC STUDY - Markhamah Markhamah (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2020)
This article aims to identify Muhammad’s linguistic characters as a speech partner and speaker in the Quran. Objects of this research are verses in Quran translation texts containing Muhammad's role as a speech partner and speaker. Data were collected using observation and documentation techniques and analyzed using the referential identity method. The study found that Muhammad's characters as a speech partner and speaker in Quran translation texts contain many educational values applicable to language ethics. They include: utilizing trusted source as information basis of using language, being a trustworthy communicator of language, integrity in language and faith, not accusing without accurate information, applying proper respect to speech partners, utilization of positive tone, using the language for harmony. In conclusion, in Quran translation texts, Muhammad's linguistics characters can be utilized in language ethics education as a source of values that can be universally understood and accepted.